Impact on Macro-Benthic Communities of Hydraulic Dredging for Razor Clam Ensis minor in the Tyrrhenian Sea - Vasapollo, Claudio; Virgili, Massimo; Bargione, Giada; Petetta, Andrea; De Marco, Rocco; Punzo, Elisa; Lucchetti, Alessandro (Frontiers in Marine Science, 2020)
Bivalve molluscs fishery is of great importance along the Italian coasts, both in economic and landing terms, and different edible bivalve species are harvested both in Adriatic and Tyrrhenian Seas. A medium-term assessment of the impact of the hydraulic dredges targeting razor clam Ensis minor on macro-benthic community was made during two surveys carried out in winter 2017 and late spring – summer 2018 in central Tyrrhenian Sea, which represents the main fishing ground for this species. The study area was located between 1 and 4 m depth, within 0.3 nautical miles from the coast. A net sampler (40 cm width, 18 cm height and 14 mm mesh size) was mounted on a commercial dredge (3 m width) and enabled to collect specimens of the smallest sizes for the entire community present in the areas. A control area was identified where fishing does not occur, in order to compare exploited and not exploited sea bottoms. The results show that benthic assemblages found in dredged areas are characterized by species living in high-energy habitat, due to the closeness to the shore, and thus showing a high resilience at medium-term disturbs. Differences in species richness were not clearly evident both for the entire community and for the mollusc assemblages evaluated over the two surveys, among the control and the impacted areas, with few exceptions mainly depending on local conditions and anthropic pressure. Thus, even if the benthic community is typical of a moderately disturbed environment, the effects of fishing on the community structure are still discernible over and above the natural variation.